Soil Characteristics Under Coppice Sal (Shorea robusta) in the Lateritic Region of West Bengal - Banerjee, S. K.; Singh, Balvinder; Nath, S.; Nandi, A.; Gangopadhyay, S. K. (Indian Forester, 1989)
The nature and properties of some coppice Sal (Shorea robusta) growing soils in the lateritic region of W. Bengal were studied in order to evaluate tbe characteristics of the soils supporting this species. Out of 31 sites, 23 sites bad GBH greater than the table values suggesting tbat these sites were very much favourable for optimum growth of Sal (coppice). Ranges of some of the soil attributes suitable for the optimum growth of the species under more or less similar climatic conditions were assessed.